Lipid-mediated gating of a miniature mechanosensitive MscS channel from Trypanosoma cruzi - Jingying Zhang; Aashish Bhatt; Grigory Maksaev; Yun Lyna Luo; Peng Yuan (Nature Communications)
Abstract The mechanosensitive channel of small conductance (MscS) from E. coli (EcMscS) has served as the prevailing model system for understanding mechanotransduction in ion channels. Trypanosoma cruzi, the protozoan parasite causing Chagas disease, encodes a miniature MscS ortholog (TcMscS) critical for parasite development and infectivity. TcMscS contains a minimal portion of the canonical EcMscS fold yet maintains mechanosensitive channel activity, thus presenting a unique model system to assess the essential molecular determinants underlying mechanotransduction. Using cryo-electron microscopy and molecular dynamics simulations, we show that TcMscS contains two short membrane-embedded helices that would not fully cross an intact lipid bilayer. Consequently, drastic membrane deformation is induced at the protein-lipid interface, resulting in a funnel-shaped bilayer surrounding the channel. Resident lipids within the central pore lumen block ion permeation pathway, and their departure driven by lateral membrane tension is required for ion conduction. Together with electrophysiology and mutagenesis studies, our results support a direct lipid-mediated mechanical gating transition. Moreover, these findings provide a foundation for the development of alternative treatment of Chagas disease by inhibition of the TcMscS channel.